2011
DOI: 10.4028/www.scientific.net/msf.679-680.567
|View full text |Cite
|
Sign up to set email alerts
|

Avalanche Diodes with Low Temperature Dependence in 4H-SiC Suitable for Parallel Protection

Abstract: Avalanche diodes have been fabricated on 4H-SiC substrate. These diodes show an abrupt avalanche voltage of about 59 V which corresponds to the calculated theoretical one using our previously determined impact ionization coefficients. This avalanche voltage increases by as small as 3.7 mV/K over the investigated temperature range (150K-420K).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2012
2012
2012
2012

Publication Types

Select...
2

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…In Ref. [5] we have shown that the avalanche multiplication is the main breakdown mechanism in this kind of device and that the positive temperature coefficient is very weak. OBIC measurements have been performed on these diodes with an UV laser beam (351 nm) with a spot size of 3µm diffusing through the cratering formed by SIMS.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In Ref. [5] we have shown that the avalanche multiplication is the main breakdown mechanism in this kind of device and that the positive temperature coefficient is very weak. OBIC measurements have been performed on these diodes with an UV laser beam (351 nm) with a spot size of 3µm diffusing through the cratering formed by SIMS.…”
Section: Resultsmentioning
confidence: 99%
“…In Ref. [5] we have shown that the avalanche multiplication is the main breakdown mechanism in this kind of device and that the positive temperature coefficient is very weak.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The avalanche diodes used in this study show an abrupt avalanche breakdown voltage of about 59 V which is presented in detail in a previous paper [4]. To perform OBIC measurements, optical windows have been opened on the anode metallizations by using the Secondary Ion Mass Spectrometry (SIMS) technique [5].…”
Section: Methodsmentioning
confidence: 99%